Theological Value in the Bakaua Ritual Tradition in the Sacred Graveyard: A Case Study in Nagari Sungai Limau, Dharmasraya Regency - Muhammad Yusuf; Gazali Gazali (Proceeding of The International Conference on Religious Education and Cross - Cultural Understanding, 2025)
This article explains the Bakaua ritual at sacred graves, a tradition of the Nagari Sungai Limau community that has deep theological value. This research aims to analyze the meaning of theological values in the Bakaua ritual and how its practice can strengthen people's spiritual relationships. Using a descriptive qualitative approach, this research examines the spiritual, social, and cultural aspects inherent in the Bakaua tradition. The research results indicate that this ritual serves not only as a means of prayer and respect for ancestors but also as a medium for strengthening social relations and preserving local wisdom. Apart from that, the Bakaua ritual is seen as a form of asking for protection, expressing gratitude, and fulfilling vows, which reflects the close relationship between culture and theology in the life of Minangkabau society. The method used in this research is qualitative, encouraging a different approach from previous research, which only discussed Bakaua dramaturgy in the Minangkabau society. However, this paper places more emphasis on aspects of theological values in the Bakaua ritual tradition at sacred graves. This study highlights how theological meaning is embodied through symbolic practices, offerings, and communal prayers that represent submission to divine will. It also reveals how the ritual facilitates intergenerational transmission of spiritual values, maintaining continuity of belief systems in modern contexts. By analyzing community participation and oral narratives, the research uncovers deep spiritual motives rooted in Islamic beliefs intertwined with local cultural expressions. In addition, the findings underscore the community’s resilience in preserving traditional theology-based rituals despite the influence of modernization and shifts in religious interpretations. The Bakaua ritual thus becomes a cultural-theological bridge that binds generations and sustains spiritual identity within the dynamic life of the Minangkabau people.